ANALISIS TINDAK TUTUR DALAM KEGIATAN BERBICARA PADA PEMBELAJARAN TEKS BERITA SEBAGAI ALTERNATIF BAHAN AJAR KELAS VIII SMP PASUNDAN 8 BANDUNG - Fitra Noviandara; Any Budiarti; Marlia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Speaking skills need to be developed and learned by everyone because speaking skills are very important in communicating. Likewise in the learning process, it is necessary to practice in the form of oral communication. The problem here is the lack of students' speaking skills in discussing or presenting. Some of the factors experienced by students in speaking skills include low self-confidence, lack of mastery of the material, uncomfortable situations and conditions, and lack of language knowledge so that from some of these factors students have not been able to convey ideas, ideas or goals fluently that can be understood. by listeners. This research needs to be done to find out the realization of students' speech acts when speaking activities in news text learning. The approach used in the study uses descriptive qualitative research methods. The results obtained, the realization of illocutionary and perlocutionary speech acts is found in speaking activities during news text learning.